(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
SAMs have become one of the most essential materials in the modern inverted PSCs‚ setting the stage for molecular engineering at interfaces through simple scalable processing․ In this review‚ we summarize the advancements that exploit SAMs as hole transport layers in the inverted (p-i-n) PSCs‚ addressing the outstanding challenges of molecular packing‚ adhesion to metal oxides‚ and wetting from polar precursors of the perovskite layer․ We will highlight seven recent works from Chen et al․‚ Li et al․‚ Du et al․‚ Ahmmed et al․‚ Wang et al․‚ Yuan et al․‚ and Huang et al․ for passivating surface defects with ligands‚ changing the core of the SAM to improve its dipole and binding energy‚ coupling SAMs to polymer or carbonaceous layers to exploit their advantages and compensate for their weaknesses‚ and replacing incompatible carbazole-based anchoring groups with stronger ones․ All these strategies have delivered PCEs beyond 26% and meaningful operational stability improvements under accelerated aging․ In this Review we describe what worked‚ what didn't and argue that‚ rarely‚ a single fix solves all the problems․ Rather the most effective interventions often use a combination of approaches․ We conclude the review with some thinking about where the field is currently challenged‚ and where future gains are likely․